Self-assembled nanoparticles of dextrin substituted with hexadecanethiol - Gonçalves, Catarina (2007)
The amphiphilic molecule dextrin-VA-SC16 (dexC16) was synthesized and studied in this work. DexC16 has a hydrophilic dextrin backbone with grafted acrylate groups (VA) substituted with hydrophobic 1- exadecanethiol (C16). A versatile synthetic method was developed allowing control of the dextrin degree of substitution with the hydrophobic chains (DSC16, number of alkyl chains per 100 dextrin glucopyranoside residues). Materials with different DSC16 were prepared and characterized using 1H NMR. DexC16 self-assembles in water through association of the hydrophobic alkyl chains, originating nanoparticles. The nanoparticles properties were studied by dynamic light scattering (DLS), fluorescence spectroscopy, and atomic force microscopy (AFM).